Evolución del gasto público social y su influencia en la reducción de la pobreza en Colombia 2002-2014 (2016)
This research is general objective to study the influence of the Social Public expenditure on Poverty reduction for the period 2002 - 2014, taking into account that in this period was that it began implementing the classification of public expenditure (2002) and also generated a methodological change in the measurement of poverty in 2006 and 2007, is for this reason that it is appropriate to determine the influence that comes to have GPS on poverty.